2022
DOI: 10.1111/fme.12605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated water temperature on cutthroat trout angler catch rates and catch‐and‐release mortality in Idaho streams

Abstract: The concern is growing that angling may need to cease at elevated summer water temperatures to protect salmonid populations. Cutthroat Trout Oncorhynchus clarkii in streams were caught, marked and released using artificial dry flies at temperatures from 13.5 to 25.7°C to evaluate whether subsequent recapture with backpack electrofishing (an index of relative survival) was reduced when the water temperature was elevated at the time of landing, and to evaluate the effect of water temperature on angler catch rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Meyer et al. (2023) found that angler catch of stream‐dwelling trout was reduced at higher temperatures. As such, Meyer et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meyer et al. (2023) found that angler catch of stream‐dwelling trout was reduced at higher temperatures. As such, Meyer et al.…”
Section: Discussionmentioning
confidence: 99%
“…As such, Meyer et al. (2023) noted that population‐level influences from catch‐and‐release angling may be higher at lower temperatures as a result of increased angler catch rates. Though some catch‐and‐release steelhead fisheries do exist at times when steelhead are exposed to water temperatures exceeding 19°C, few steelhead are present in Idaho during such fisheries, steelhead are likely seeking coolwater refuges, and fish may be less susceptible to being caught.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation